Depression and Anxiety in Chronic Kidney Disease Patients Undergoing Hemodialysis Therapy at Hemodialysis Installations General Hospital Dr. Moewardi Surakarta - Dini Darayani Husni Putri; Indro Nugroho (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
This study is an analytical descriptive study with a cross-sectional design that aims to determine the proportion and level of depression and anxiety of patients, as well as the relationship between the length of hemodialysis therapy with depression and anxiety of patients with Chronic Kidney Disease undergoing hemodialysis therapy at the Hemodialysis Installation of Dr. Moewardi Surakarta Regional General Hospital. Samples in this study were taken by purposive sampling. The sample in this study amounted to 31 research subjects. The specified data analysis is a Chi-square test analysis to test the relationship between variables. The percentage of anxiety among Chronic Kidney Disease patients receiving hemodialysis treatment at Dr. Moewardi Surakarta Regional General Hospital's Hemodialysis Facility is 29%, while the percentage of depressed patients with Chronic Kidney Disease undergoing hemodialysis therapy at the same facility is 41.9%. It has been determined that there is no discernible correlation between the duration of hemodialysis therapy and the emergence of anxiety and depression in patients with Chronic Kidney Disease at this specific healthcare center. To gain a more comprehensive understanding, additional research is warranted to investigate other factors linked to anxiety and depression in patients with chronic kidney disease undergoing hemodialysis therapy. Furthermore, there is a pressing need for the implementation of a screening program for Chronic Kidney Disease patients undergoing hemodialysis therapy at hospitals, with a potential referral to the Department of Psychiatry for the assessment and management of any mental symptoms that may arise. Keyword: Anxiety, Chronic kidney disease, Depression